2007
DOI: 10.1016/j.rapm.2006.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Single-Injection Brachial Plexus Anesthesia for Arteriovenous Fistula Surgery of the Forearm: A Comparison of Infraclavicular Coracoid and Axillary Approach

Abstract: Blockade of the musculocutaneous nerve developed faster with the infraclavicular coracoid approach than with the axillary approach. The infraclavicular coracoid approach may be preferable in patients scheduled for the creation of an arteriovenous fistula at the forearm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…However most sensory blocks become fixed at 30 min whereas motor distal blocks continue to progress. Niemi et al [ 18 ] evaluated the IBPB at 60 min after the injection of the block for the efficacy and found adequate surgical anesthesia ranging from 90% to 97% in the various nerve territories with absence of maximum block until 45 min. Delayed effect or evolving block even after 30 min could have resulted in partial effect in the patients receiving dexamethasone, particularly in the failed cases and cannot be ruled out since we waited only 30 min for the effect of the block.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However most sensory blocks become fixed at 30 min whereas motor distal blocks continue to progress. Niemi et al [ 18 ] evaluated the IBPB at 60 min after the injection of the block for the efficacy and found adequate surgical anesthesia ranging from 90% to 97% in the various nerve territories with absence of maximum block until 45 min. Delayed effect or evolving block even after 30 min could have resulted in partial effect in the patients receiving dexamethasone, particularly in the failed cases and cannot be ruled out since we waited only 30 min for the effect of the block.…”
Section: Discussionmentioning
confidence: 99%
“…Niemi et al ,[ 18 ] had observed mild tachycardia with ST segment depression in two patients who had received the axillary BPB, 10-15 min after the administration of local anesthetic. He suggested that the relative late appearance of symptoms were caused by absorption of epinephrine and attributed it to the large dose of epinephrine used (168-240 μg).…”
Section: Discussionmentioning
confidence: 99%
“…For the creation of an arteriovenous fistula for hemodialysis, succesful musculocutaneous nerve block is usually essential in order to provide adequate anesthesia as this nerve innervates the lateral aspect of the distal forearm. In cases where the exploration of blood vessels is extended distally, analgesia of the median and the radial nerve may also be required [3]. …”
Section: Discussionmentioning
confidence: 99%
“…In one study, Niemi et al [3] compared axillary approach and infraclavicular coracoid approach performed through single injection method for arteriovenous fistula surgeries in uremic patients. They reported that blockade of the musculocutaneous nerve developed faster with the infraclavicular coracoid approach than with the other and the infraclavicular coracoid approach may be preferable in patients scheduled for creation of an arteriovenous fistula at the forearm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation